Karyotype analysis of diploid oat germplasm introduced from Canada - Liu, W.; Zhang, Z.; Wu, B. (2013)
The chromosome karyotype of three diploid oat species was studied with squash method. The results showed that the karyotype formula of Avena strigosa was 2n=2x=14=10m+4sm(2SAT), with metacentric and submetacentric chromosomes,1 pair of satellites on the short arm of the 4th chromosome and 68.17% for the asymmetry index; that of Avena hispanica, was 2n=2x=14=10m+4sm(2SAT), with metacentric and submetacentric chromosomes, 1 pair of satellites on the short arm of the 7th chromosome and 59.31% for the asymmetry index ;and that of Avena brevis was 2n=2x=14=6m+4sm+4st(2SAT), with acrocentric,metacentric and submetacentric chromosomes, 1 pair of satellites on the short arm of the 6th chromosome and 63.91% for the asymmetry index . Although the karyotypes of all three species were 2A type, there was obvious variation in the morphologies of karyotypes of three species, which comparatively indicated that the karyotype of Avena strigosa was more advanced in evolution, followed by Avena brevis and the karyotype of Avena hispanica was more original. This study will be a useful reference for the karyotype analysis and evolutionary analysis of oat germplasm resources.